Makna Fi’il Madhi dan Mudhari’ dalam Redaksi Al-Qur’an - Syamsul Hidayat; Ferdianur Ferdianur; Ahmad Dasuki (Jurnal Teologi Islam, 2026)
This study aims to analyze the use of fi’il madhi and fi’il mudhari’ in the Qur'anic discourse along with their theological and rhetorical implications. In Arabic grammar, these two verb forms function not only as tense indicators but also carry profound dimensions of meaning according to the context of the verse. This research employs a descriptive qualitative method with a library research approach. The results indicate that fi’il madhi in the Qur'an is frequently used to emphasize certainty, even for future events guaranteed by Allah SWT. On the other hand, fi’il mudhari’ is utilized to denote continuity, renewal, and dynamic vivid description. A deep understanding of these verb form transitions is a crucial key in the science of tafsir to fully grasp moral, legal, and creedal messages. This analysis proves that every choice of diction in the Qur'an possesses linguistic precision that reinforces its linguistic miracle.